The PEMBERDAYAAN MASYARAKAT KELURAHAN KADIPIRO DAN NUSUKAN KOTA SURAKARTA DALAM PENANGANAN SAMPAH ORGANIK MELALUI BUDIDAYA MAGGOT (Hermetia illucens) - pramono hadi hadi; Tri Rahayu; Hafid Zakaria; Suharno Suharno; Siti Nurlela; Sarsono Sarsono (LP2M STP Mataram, 2021)
ABSTRACK Increasing the consumption of animal protein for the community during the Covid-19 pandemic is very important. A very easy and cheap source of protein for the community is chicken. The problem in raising chickens is the problem of feed, especially if the chicken feed has to be purchased at a production facility shop. On the other hand, organic waste or organic waste in households is very abundant and even becomes environmental problems such as: odor, dirty and also disturbs beauty. An alternative solution to the problem of organic waste is through maggot cultivation as an animal that is able to convert organic waste into organic fertilizer, both solid and liquid. In addition, maggot itself has a high protein content of (40-50)%. This community empowerment method is carried out by providing assistance and training to the community with regular communication and periodic supervision. For people who are good and able to cultivate yam maggot funds in Kadipiro and Nusukan, Banjarsari districts, Surakarta municipality from September to December 2020. The results of this community service resulted that maggot was able to substitute for factory chicken feed by 50%, resulting in a savings rate of 50% of the total production costs in raising chickens. So that maggot can be recommended as natural chicken feed that is environmentally friendly and improves chicken health. Keywords: maggot, organic waste, community empowerment